Spinel catalyst as well as preparation method and application thereof
By using high-entropy spinel catalysts, the problems of low catalytic performance and low durability of existing catalysts when removing sulfur-containing volatile organic pollutants are solved, and efficient and long-lasting ozone catalytic oxidation effect is achieved.
Patent Information
- Application Number
- CN202411541985.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-10-31
AI Technical Summary
When the existing ozone catalytic oxidation catalysts remove sulfur-containing volatile organic pollutants (S-VOCs), they have low catalytic performance and low durability, which limits the development of ozone catalytic environmental restoration.
A high-entropy spinel catalyst is used, and its chemical formula is M1Co2O4, where M is a doped metal, any one or more of Fe, Ni, Cu, Zn, Mn, and Cr. The ozone catalytic oxidation reaction is promoted through the multimetallic high-entropy coordination synergistic effect.
It significantly improves the effect of ozone catalytic oxidation to remove S-VOCs, has high catalytic performance and strong durability, can remove CH3SH 100% and maintain a removal efficiency of more than 80% after 24 hours.
Smart Images

Figure CN119588362A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalysts, and more specifically, to a spinel catalyst and a preparation method and application thereof. Background Art
[0002] Odor-emitting and toxic waste gases include a variety of sulfur-containing volatile organic compounds (S-VOCs), which pose a significant threat to the ecological environment and human health. In order to cope with increasingly stringent environmental regulations, ozone catalytic oxidation to remove VOC technology has become a research focus. This technology provides a promising solution for the deep purification of low-concentration and difficult-to-degrade waste gases due to its economic feasibility and efficiency. Existing ozone activation catalysts require complex synthesis routes and complex process methods, and have low performance and low persistence in catalytic ozonation of volatile organic pollutants, which greatly limits the development of ozone catalytic environmental remediation, especially the ozone catalytic oxidation of gaseous S-VOCs.
[0003] The prior art discloses a catalyst for ozone oxidation and decomposition of organic pollutants in water and a method for catalyzing ozone treatment of sewage. The catalyst for ozone oxidation and decomposition of organic pollutants in water is spinel ferrite M 1-x N x Fe2O4, wherein 0<x<1, M and N are any of the metal elements Ni, Mn, Co, Zn, Mg, Cu, Cr, Pb, Sr, Ba and Ca, and M and N are different elements. It discloses the use of spinel ferrite as a catalyst for ozone oxidation and decomposition of organic pollutants in water. It discloses the technology of using spinel ferrite as an ozone catalytic oxidation catalyst, but it is not aimed at the ozone catalytic oxidation of sulfur-containing volatile organic pollutants, and does not solve the problem of low catalyst performance and low durability of ozone catalytic oxidation of sulfur-containing volatile organic pollutants. Summary of the invention
[0004] The purpose of the present invention is to overcome the defects and shortcomings of the existing catalysts used for ozone catalytic oxidation to remove volatile organic pollutants, especially sulfur-containing volatile organic pollutants, such as low performance and low persistence, and to provide a spinel catalyst that can significantly improve the ozone catalytic oxidation to remove volatile organic pollutants, especially the removal effect of sulfur-containing volatile organic pollutants S-VOCs, and has high catalytic performance and strong persistence.
[0005] Another object of the present invention is to provide a method for preparing a spinel catalyst.
[0006] Another object of the present invention is to provide an application of a spinel catalyst in ozone catalytic oxidation.
[0007] The above-mentioned purpose of the present invention is achieved through the following technical solutions:
[0008] A high entropy spinel catalyst, characterized in that its chemical formula is: M1Co2O4, wherein M is a doped metal, which is any one or more of Fe, Ni, Cu, Zn, Mn, and Cr, but not Zn alone.
[0009] It should be noted that:
[0010] The metal occupancy in the spinel structure is alternating between tetrahedral sites and octahedral sites, with valences of +2 and +3 respectively. The structure of spinel is defined as A1B2O4, where A represents the tetrahedral +2 site and B represents the octahedral +3 site. Different divalent metals are doped into it to replace the original metal at the +2 site.
[0011] The spinel catalyst of the present invention has a pure single-phase spinel structure, and the spinel phase has a consistent particle morphology and uniform particle size, so that the catalyst has appropriate oxygen vacancies, which is more conducive to ozone catalytic oxidation reaction.
[0012] The spinel catalyst of the present invention is a specific multi-metal doped spinel having a specific multi-metal high-entropy coordination synergistic effect. The high-entropy coordination and electron coupling effects lead to a high spin state of Co at the active site, which accelerates the breaking of the OO bond of ozone and promotes the formation of a key intermediate M-*O between the broken oxygen and the metal element of the catalyst, thereby establishing a non-radical mediated interfacial catalytic reaction.
[0013] In heterogeneous catalytic ozonation, the ozone catalytic pathway includes free radical-based oxidation (·OH / O2· - ) and non-radical oxidation ( 1 O2, *O and *O2). The high entropy spinel catalyst of the present invention uses surface O as the main active substance in the ozone activation system. Compared with the traditional free radical mediated process, the oxygen species *O and *O2 adsorbed on the surface have higher average potentials of 2.43V and 1.35V respectively, and the mineralization of organic pollutants is more thorough. It also has higher selectivity and fewer side reactions, which significantly improves the catalytic efficiency. In addition, compared with transient free radicals, the longer life of the oxygen species *O formed by ozone breakage contributes to continuous oxidation.
[0014] In order to achieve a better multi-metal high-entropy coordination synergistic effect, preferably, the number of the doping metals M is greater than or equal to 4.
[0015] In a preferred embodiment, the spinel catalyst of the present invention is doped with 4 or more different types of metal elements to form a high entropy spinel catalyst, and the overall metal types are 5 or more. Through the high entropy configuration (doping of multiple metal elements, the octahedral Co site reaches a high spin state through electronic interaction, and the interaction with ozone is enhanced to form an M-*O bond, so as to realize a non-radical, that is, a non-radical activation path of surface *O, realize precise regulation of the active site, and highly selectively induce a non-radical generation path, which is more conducive to ozone catalytic oxidation.
[0016] In another specific embodiment, the spinel catalyst of the present invention can be, for example: (Fe)1Co2O4, (Ni)1Co2O4, (Cu)1Co2O4 or (FeNiCuZn)1Co2O4.
[0017] The present invention also specifically protects a method for preparing a spinel catalyst, comprising the following steps:
[0018] S1. Mixing Na2CO3 solution, cobalt salt solution and M metal salt solution dropwise to obtain a mixed solution, adjusting the pH of the mixed solution to a precipitation pH, and reacting to obtain a precipitate,
[0019] S2. Calcine the precipitate at 400-700° C. for 2-4 h to obtain a spinel catalyst.
[0020] It should be noted that:
[0021] In the preparation method of the spinel catalyst of the present invention, the preparation of the multi-metal doped spinel catalyst can be achieved by controlling the time and temperature of the precipitate roasting reaction, and the crystallinity of the spinel catalyst can be optimized and controlled. The appropriate crystallinity can make the catalyst maintain the crystal form of the spinel and have an appropriate disorder after metal doping, and can also make the catalyst have appropriate oxygen vacancies, which is beneficial to the catalytic reaction.
[0022] In a specific embodiment, the pH value can be adjusted to 9 in step S1.
[0023] In a specific embodiment, preferably, the calcination temperature in S2 is 600° C. and the calcination time is 3 h.
[0024] The present invention also specifically protects the use of a high entropy spinel catalyst in ozone catalytic oxidation.
[0025] In the application of the present invention, the high entropy spinel catalyst can establish a non-radical mediated interfacial catalytic reaction, and the mineralization of organic pollutants in the ozone catalytic oxidation reaction is more thorough, with higher selectivity and fewer side reactions, effectively solving the problem of limited catalytic efficiency. The catalytic persistence is stronger, and it is more capable of promoting the complete degradation of VOCs by ozone catalytic oxidation.
[0026] Furthermore, the high entropy spinel catalyst of the present invention can be recycled. After cyclic catalysis, the catalyst can still maintain a relatively high catalytic activity, is easy to recover, and can be reused through regeneration, so it is an environmentally friendly material.
[0027] In a specific embodiment, the high entropy spinel catalyst of the present invention is particularly suitable for ozone catalytic oxidation of sulfur-containing volatile organic pollutants S-VOCs.
[0028] The sulfur-containing volatile organic pollutants S-VOCs of the present invention particularly refer to gaseous S-VOCs targeting CH3SH gas.
[0029] In a specific embodiment, in order to achieve a better ozone catalytic oxidation treatment effect, preferably, the concentration of CH3SH in the CH3SH gas is 40 to 60 ppm.
[0030] In a specific embodiment, the high entropy spinel catalyst of the present invention can be applied to treat gas S-VOCs with CH3SH gas of different humidity as the target gas, especially high humidity CH3SH gas. Preferably, the ambient humidity in the application is ≥60%, for example, 75%.
[0031] In a specific embodiment, in order to achieve a better ozone catalytic oxidation treatment effect, preferably, the concentration of ozone in the application is 30 to 60 ppm, for example, 40 ppm.
[0032] The dosage of the high entropy spinel catalyst of the present invention is preferably 5 to 10 mg.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] The spinel catalyst of the present invention is a multi-metal doped spinel, which has a multi-metal high entropy coordination synergistic effect. The high entropy coordination and electronic coupling effects lead to a high spin state of Co in the active site, which accelerates the breaking of the OO bond and promotes the formation of the key intermediate M-*O. A non-radical-mediated interfacial catalytic reaction is established, which makes the mineralization of organic pollutants more thorough, has higher selectivity and fewer side reactions, and can effectively solve the problem of limited catalytic efficiency. In addition, compared with transient free radicals, the longer life of O contributes to continuous oxidation and promotes the complete degradation of VOCs.
[0035] The spinel catalyst of the present invention exhibits significant catalytic activity, can remove CH3SH by 100% under high humidity conditions, and maintains a removal efficiency of more than 80% after 24 hours, having good durability. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 The degradation effect diagram of different catalysts.
[0037] Figure 2 These are the catalytic results under different gas atmospheres.
[0038] Figure 3 This is the persistence test result diagram.
[0039] Figure 4 This is the SEM test result.
[0040] Figure 5 This is the X-ray diffraction test result diagram.
[0041] Figure 6 This is the in-situ infrared detection result.
[0042] Figure 7 This is the in-situ Raman detection result. DETAILED DESCRIPTION
[0043] The present invention is further described below in conjunction with specific embodiments, but the embodiments do not limit the present invention in any form. Unless otherwise specified, the raw materials and reagents used in the embodiments of the present invention are conventionally purchased raw materials and reagents.
[0044] Example 1
[0045] A spinel catalyst, with a chemical formula of (FeNiCuZn)1Co2O4, denoted as HE-Co3O4, is prepared as follows:
[0046] S1. Dissolve 5 mmol of Na2CO3 in 100 ml of deionized water, stir well and pour into a reagent bottle for later use;
[0047] Meanwhile, 5 mmol of a mixed metal salt is dissolved in 100 ml of deionized water, wherein the mixed metal salt is divalent nitrates of cobalt, iron, nickel, copper and zinc, and stirred until completely dissolved to obtain a mixed solution, wherein the mass ratio of the divalent nitrates of cobalt, iron, nickel, copper and zinc in the mixed metal salt is 2:0.25:0.25:0.25:0.25,
[0048] Then the above two solutions were dropped into 50 ml of deionized water, and the pH value was carefully controlled to be maintained at 9.5 during the whole process. Stirring was continued for 1 hour, after which the precipitate was collected by suction filtration and rinsed with deionized water to remove excess metal ions.
[0049] S2. The washed precipitate is dried for 12 hours, and then calcined in a tubular furnace at 600°C (5°C / min) for 3 hours in an air atmosphere. During the calcination process, after the metal enters, due to the change in the coordination environment, a portion of the Co valence state increases to trivalent, and (FeNiCuZn)1Co2O4 is obtained.
[0050] Example 2
[0051] A spinel catalyst, with a chemical formula of (Fe)1Co2O4, is prepared by the same method as in Example 1, except that the mixed metal salts are cobalt nitrate and iron nitrate, with a molar ratio of 2:1.
[0052] Example 3
[0053] A spinel catalyst, with a chemical formula of (Ni)1Co2O4, is prepared by the same method as in Example 1, except that the mixed metal salts are cobalt nitrate and nickel nitrate, with a molar ratio of 2:1.
[0054] Example 4
[0055] A spinel catalyst, with a chemical formula of (Cu)1Co2O4, is prepared by the same method as in Example 1, except that the mixed metal salts are cobalt nitrate and copper nitrate, with a molar ratio of 2:1.
[0056] Example 5
[0057] A spinel catalyst, with a chemical formula of (FeNiCuZn)1Co2O4, denoted as HE-Co3O4, is prepared by the same method as in Example 1, except that the calcination temperature is 600°C.
[0058] Example 6
[0059] A spinel catalyst has a chemical formula of (FeNiCuZn)1Co2O4 and is prepared by the same method as in Example 1, except that the metal salts are cobalt nitrate and iron nitrate at 700°C.
[0060] Example 7
[0061] An application of a spinel catalyst in ozone catalytic oxidation, the specific application method is as follows:
[0062] In the catalytic ozonation of CH3SH, the reaction was carried out in a continuous flow fixed bed reactor at room temperature. A 10 mg catalyst sample was placed in the reactor and the total gas flow rate was set to 100 ml / min. The inlet gas humidity was adjusted to 50% by a humidity generator, and ozone was produced by an ozone generator (YDG, YE-TG-02PII) with a concentration of 40 ppm and an ozone flow rate of 10 ml / min. CH3SH was introduced by mixing 1000 ppm of CH3SH (diluted with nitrogen) with clean air at a concentration of 50 ppm. After the inlet concentration (C0) of CH3SH was stabilized, the catalyst was added and the outlet concentration (C) was monitored using a CH3SH sensor.
[0063] The outlet gas is collected in a gas bag and analyzed for composition using a proton transfer reaction time-of-flight mass spectrometer. Exhaust gas treatment is performed using spent catalyst and activated carbon to reduce atmospheric pollution.
[0064] The spinel catalysts of Examples 1-6 were respectively applied in the above-mentioned catalytic applications.
[0065] The specific catalytic effects are shown in Table 1 and Figure 1 As shown:
[0066] Table 1
[0067] Example <![CDATA[CH3SH removal rate]]> 1 100% 2 48% 3 82% 4 80% 5 90% 6 76%
[0068] Example 8
[0069] An application of a spinel catalyst in ozone catalytic oxidation, the specific application method is as follows:
[0070] The method is applied in accordance with Example 7, except that the amount of catalyst HE-Co3O4 used is 5 mg.
[0071] The CH3SH removal rate was determined to be 72%.
[0072] Example 9
[0073] An application of a spinel catalyst in ozone catalytic oxidation, the specific application method is as follows:
[0074] The method is applied in accordance with Example 7, except that the amount of catalyst HE-Co3O4 used is 7.5 mg.
[0075] The CH3SH removal rate was determined to be 81%.
[0076] Example 10
[0077] An application of a spinel catalyst in ozone catalytic oxidation, the specific application method is as follows:
[0078] The application is carried out in accordance with Example 7, except that the humidity condition is 0.
[0079] The CH3SH removal rate was determined to be 100%.
[0080] Embodiment 11
[0081] An application of a spinel catalyst in ozone catalytic oxidation, the specific application method is as follows:
[0082] The application was carried out in accordance with Example 7, except that the humidity condition was 25%.
[0083] The CH3SH removal rate was determined to be 100%.
[0084] Example 12
[0085] An application of a spinel catalyst in ozone catalytic oxidation, the specific application method is as follows:
[0086] The application was carried out in accordance with Example 7, except that the humidity condition was 75%.
[0087] The CH3SH removal rate was determined to be 100%.
[0088] Example 13
[0089] An application of a spinel catalyst in ozone catalytic oxidation, the specific application method is as follows:
[0090] The method is applied with reference to Example 7, except that the ozone gas is replaced with other gas atmospheres, including N2 atmosphere and O2 atmosphere.
[0091] The results of the test are as follows Figure 2 As shown in the figure, it can be seen that the spinel catalyst of the present invention can significantly catalyze and activate ozone to degrade CH3SH, rather than activating other gases in the air.
[0092] Example 14 Durability and stability test
[0093] An application of a spinel catalyst in ozone catalytic oxidation, the specific application method is as follows:
[0094] Refer to Example 8 for application.
[0095] The persistence test results are as follows Figure 3 As shown in the figure, it can be seen that the spinel catalyst of the present invention has a good recycling effect. Its catalytic efficiency remains basically unchanged after three cycles, and it maintains a removal efficiency of about 90% after 24 hours, showing good durability.
[0096] Comparative Example 1
[0097] A spinel catalyst, without any doping of the above-mentioned related metal elements, has a chemical formula of Co3O4, and a specific preparation method is as follows:
[0098] S1. Dissolve 5 mmol of Na2CO3 in 100 ml of deionized water, stir well and pour into a reagent bottle for later use;
[0099] Meanwhile, dissolve Co(NO3)2·6H2O in 100 ml of deionized water and stir until completely dissolved.
[0100] Then the above two solutions were dropped into 50 ml of deionized water, and the pH value was carefully controlled to be maintained at 9.5 during the whole process. Stirring was continued for 1 hour, after which the precipitate was collected by suction filtration and rinsed with deionized water to remove excess metal ions.
[0101] S2. The washed precipitate was dried for 12 hours and then calcined in a tube furnace at 600°C (5°C / min) for 3 hours in an air atmosphere to obtain Co3O4.
[0102] Refer to Example 7 for application.
[0103] The CH3SH removal rate was determined to be 20%.
[0104] Comparative Example 2
[0105] A spinel catalyst has a chemical formula of (Ni)1Co2O4 and is prepared by the same method as in Example 1, except that the metal salts are cobalt nitrate and nickel nitrate.
[0106] Refer to Example 7 for application.
[0107] The CH3SH removal rate was determined to be 21%.
[0108] Results
[0109] (1) Scanning electron microscope (SEM) inspection
[0110] The spinel catalysts of Examples 1 to 5 were tested by scanning electron microscope (SEM). The test results are as follows: Figure 4 shown.
[0111] Scanning SEM images showed that all spinel phases had consistent particle morphology and uniform particle size.
[0112] (2) X-ray diffraction (XRD) test
[0113] The crystallinity of the spinel catalyst was tested by XRD. The test results are as follows: Figure 5 As stated, Figure 5 The XRD pattern in shows diffraction peaks on the (220), (311), (222), (400), (511), and (440) planes with 2θ values of 31.58°, 37.19°, 38.40°, 44.64°, 59.54°, and 65.21°, which can be identified as belonging to The cubic spinel phase of space group (JCPDS: PDF#42-1467) 29-31 was not detected for the diffraction peaks of Fe, Ni, Co, and Zn metal oxides, indicating that HE-Co3O4 has a pure single-phase spinel structure. Other synthesized binary cobalt-based spinel oxides, including Fe1Co2O4, Ni1Co2O4, Co1Co2O4, and Ze1Co2O4, also show similar crystal structures.
[0114] (3) Product analysis: in situ infrared.
[0115] In the comparative example, the ozonation of CH3SH catalyzed by Co3O4 and HE-Co3O4 was analyzed by in situ DRIFTS. Figure 6 As described above, it was found that in the HE-Co3O4 catalytic reaction, CH3SH molecules were oxidized into a series of intermediates, including SO, sulfate, sulfonate and sulfite, and finally completely mineralized into inorganic substances. In the Co3O4 catalytic reaction, the oxidation of CH3SH was relatively weak, and toxic intermediates such as CH3SSCH3 and CH3SO 3- It gradually accumulates on the catalyst surface, indicating that the breaking of the CS bond is the limiting step of CH3SH mineralization and is also the reason for the deactivation of the Co3O4 catalyst in Comparative Example 1.
[0116] (3) In-situ Raman, quenching experiments and ESR testing
[0117] In order to fully prove that ozone is activated through the non-radical pathway of surface atom *O, the generation of the key intermediate M-*O was detected by in situ Raman, free radical quenching experiments and ESR tests were performed, and the non-radical contribution rates of different catalytic systems were compared. The test results are as follows Figure 7 As shown, from Figure 7 It can be seen that, in general, ·OH, 1 O 2, O2 ·- The contribution of *O is very small, and *O is the main active species in this system. This shows that the ozone activation pathway of the catalyst of the present invention is a non-radical activation pathway of surface *O.
[0118] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A spinel catalyst, characterized in that Its chemical formula is: M1Co2O4, wherein M is a doping metal, which is any one or more of Fe, Ni, Cu, Zn, Mn, and Cr, but not Zn alone.
2. The spinel catalyst according to claim 1, characterized in that The number of types of the doping metal M is greater than or equal to 4.
3. A method for preparing the high entropy spinel catalyst according to claim 1 or 2, characterized in that: The steps include: S1. Mixing Na2CO3 solution, cobalt salt solution and M metal salt solution dropwise to obtain a mixed solution, adjusting the pH of the mixed solution to a precipitation pH, and reacting to obtain a precipitate, S2. Calcine the precipitate at 400-700° C. for 2-4 h to obtain a spinel catalyst.
4. The preparation method according to claim 3, characterized in that: The calcination temperature in S2 is 600°C and the time is 3h.
5. Use of the high entropy spinel catalyst according to claim 1 or 2 in ozone catalytic oxidation.
6. The use according to claim 5, characterized in that The application is ozone catalytic oxidation of sulfur-containing volatile organic pollutants.
7. The use according to claim 6, characterized in that The sulfur-containing volatile organic pollutant is CH3SH gas.
8. The use according to claim 7, characterized in that The concentration of the CH3SH gas is 40 to 60 ppm.
9. The use according to claim 7, characterized in that: The application environment humidity is ≥ 60%.
10. The use according to claim 7, characterized in that: The concentration of ozone in the application is 30-50 ppm.
Citation Information
Patent Citations
Catalyst for oxidation and decomposition of organic pollutants in water with ozone and method thereof for catalyzing sewage treatment with ozone
CN102151567A
Fe and Ni co-substituted cobalt-based spinel type wave-absorbing material, preparation method and application thereof
CN108910963A
Cerium-Cobalt Spinel System as ZPGM Composition for DOC Applications
US20160263561A1
Cited By
Zn / Cu modified Co-based catalyst as well as preparation method and application thereof
CN121372408A